Prevalence of Neonatal Diseases in Multan Region, Pakistan - Tabassum, Sana; Amin, Muhammad; Akram, Muhammad; Aman Ullah, Muhammad (Pakistan Journal of Nutrition, 2013)
Neonatal death rates and morbidity is forever a high interest for doctors and public health specialist. Main objectives of this research is to determine the prevalence of neonates diseases in Multan region, to make assessment which disease has been most commonly occurring in this region and finally present comparison of neonatal diseases proportion by gender. This study was carried out in the Children ward, Nishter Hospital, Multan from 1st January to 31st July 2012 and data of all admitted neonates were recorded. Descriptive statistics and z-test was used for the comparison of proportion of neonatal diseases by gender. A total of 889 neonates patients were observed during this period which comprises 535 (60.18%) male and 354 (39.82%) female. Of the all neonatal diseases, Birth asphyxia (B.A) was the most frequent i.e., 424 (47.69%) patients. Preterm babies were 168 (18.90%) and babies with sepsis were 155 (17.44%). Tetanus followed 12 (1.35%), Meconium Aspiration Syndrome (MAS) 28 (3.15%) babies and babies who born premature were 46 (5.17%). From z-test, we have found that all neonatal diseases by gender are significant. In our study Birth asphyxia, preterm, prematurity, MAS, sepsis, and tetanus are the main causes of neonatal admissions, while preterm birth, birth asphyxia and sepsis are in great proportion. When comparison was made, it was revealed that the prevalence of all neonatal diseases is higher among male neonates than female except in MAS neonates. The Solid and supportable policies are required to formulate and carried out to escape from numerous preventable reasons of neonatal morbidity and mortality.